2016
DOI: 10.1016/j.jams.2015.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Improves Insulin Resistance by Reducing Neuroprotein Y/Agouti-Related Protein Levels and Inhibiting Expression of Protein Tyrosine Phosphatase 1B in Diet-induced Obese Rats

Abstract: Electroacupuncture (EA) has been shown to exert beneficial effects on obesity, but the mechanism is unclear. This study investigated the effects of EA on diet-induced obese (DIO) rats. Fifty male Sprague-Dawley rats were randomly divided into low-fat diet (LFD, 10 rats) and high-fat diet (HFD, 40 rats) groups. After the DIO models had been established, successful model rats were randomly divided into HFD, EA, and orlistat (OLST) groups. The EA group received EA at Zusanli (ST36) and Quchi (LI11) for 20 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One study [ 44 ] showed that downregulation of ghrelin in the stomach and neuropeptide Y (NPY) in the hypothalamus was in line with the reduction in food intake in rats receiving EA stimulation once every day. Liu et al [ 45 ] speculated that, in high-fat diet (HFD) animals, EA treatment (ST36 and LI11, 20 minutes per day for 28 days) could reduce the body weight, homeostasis model assessment-insulin resistance index, adipocyte diameters, and neuroprotein Y/agouti-related protein and protein tyrosine phosphatase 1B levels. In db/db mice, Liang et al [ 46 ] found that EA treatment (five times per week for eight weeks) contracted the increase of fasting blood glucose, food intake, and body mass and maintained insulin levels via stimulation of skeletal muscle Sirtuin 1 (SIRT1)/peroxisome proliferator-activated receptor γ coactivator 1 α (PGC-1 α ), suggesting the role of EA in improving insulin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 44 ] showed that downregulation of ghrelin in the stomach and neuropeptide Y (NPY) in the hypothalamus was in line with the reduction in food intake in rats receiving EA stimulation once every day. Liu et al [ 45 ] speculated that, in high-fat diet (HFD) animals, EA treatment (ST36 and LI11, 20 minutes per day for 28 days) could reduce the body weight, homeostasis model assessment-insulin resistance index, adipocyte diameters, and neuroprotein Y/agouti-related protein and protein tyrosine phosphatase 1B levels. In db/db mice, Liang et al [ 46 ] found that EA treatment (five times per week for eight weeks) contracted the increase of fasting blood glucose, food intake, and body mass and maintained insulin levels via stimulation of skeletal muscle Sirtuin 1 (SIRT1)/peroxisome proliferator-activated receptor γ coactivator 1 α (PGC-1 α ), suggesting the role of EA in improving insulin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, based on the data obtained in our study, the mechanism for preventing weight gain in oleacein-treated mice may be related to the amelioration of insulin resistance and the prevention of metabolic dysfunction. Weight loss related to improved insulin resistance and insulin sensitivity has been reported in diet-induced obese rats in which changes in the size of adipocytes and reduction in fat tissue were observed ( 34 ). An alternative, unexplored hypothesis, compatible with our findings, is that oleacein, like metformin ( 35 ), the first-line drug for treatment of insulin-resistant diabetes, may act by increasing energy expenditure, thus preventing weight gain.…”
Section: Discussionmentioning
confidence: 97%
“…Acupuncture, a form of TCM, has been previously reported effective in treating obesity [29][30][31][32]. Furthermore, recent years have witnessed an increasing number of clinical studies concerning the treatment of obesity using electroacupuncture [33][34][35]. Electroacupuncture was found to promote fat metabolism via sympathetic nervous system activation, thus decreasing appetite [36].…”
Section: Total (95% Ci)mentioning
confidence: 99%